A Quantitative Analysis of CRM Strategies on Customer Satisfaction and Loyalty: A Case Study in Space Rental Service Business - Yuhelsy Gayatri Evilia; Zakaria, Muhammad; Syamsul Bahri; Meutia Fadilla (TALENTA Publisher, 2025)
This study investigates how Customer Relationship Management (CRM) strategies impact customer satisfaction and loyalty within the space rental service industry. Employing a quantitative approach through Structural Equation Modeling - Partial Least Squares (SEM-PLS), this study evaluates three CRM dimensions: people, process, and technology. The data were obtained via a structured questionnaire administered to 98 respondents and analyzed using the SmartPLS software. The findings reveal that process and technology significantly affect satisfaction and loyalty, whereas the people dimension has a minor impact. Specifically, the CRM process dimension positively influences satisfaction (t = 3.184, p < 0.01) and loyalty (t = 2.590, p < 0.05), while technology shows strong effects on both (satisfaction: t = 3.696; loyalty: t = 4.850; p < 0.001). The study recommends implementing operational CRM initiatives such as call centers, feedback mechanisms, and digital engagement strategies. This work contributes to the CRM literature by offering targeted insights for physical service businesses in Indonesia.